(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2025)
The functionality of sugarcane (Saccharum officinarum) plant cells is influenced by numerous metabolic routes and cell signaling pathways. MicroRNAs (miRNAs) play critical functions in regulating production and providing protection against diverse stressors. This research focuses on identifying and partially characterizing novel miRNAs in sugarcane utilizing computational techniques, along with a preliminary assessment of their potential roles. With the help of in silico tools, 20 new non-coding miRNAs associated with 16 miRNA families were predicted. Subsequently, 5, 520 potential protein targets for these miRNAs were obtained using the psRNA Target method. Among these, 17 key targets were associated with managing metabolism, transcription, structural proteins, transport factors and cell signaling pathways. Notably, the miRNA sof-miR5169a was linked to the faciata 1-like protein process. In summary, this study highlights the identification of novel sugarcane miRNAs targeting critical genes, offering insights that may contribute to enhancing sugarcane tolerance under environmental stresses.